Education Character for Develop Child Creativity - Ni Made Cindy Wati; Dwi Nofianti Nasaru; Vita Widiyastuti Nur Rabbiyan Usman; Abdul Rahmat (Global Scientific Publishing, 2022)
Creativity of course not a factor main in education but good education is capable education stimulate his students for develop his creativity . Creativity is characteristic courage echoing human who himself and what Becomes what man later day . Creativity rooted in curiosity and openness _ natural individual when exploring the world around him and searching know about himself . So creativity child is very important for development next because of childhood was a very influential period towards the next . Destination study this among them for answer : 1 ). Description the trouble it causes child not enough could develop creativity , 2). Picture that environment could influence development creativity child age early .
Keywords: Education; Character; Creativity